PERINTISAN USAHA BERSAMA DI BIDANG PRODUKSI PUPUK ORGANIK BAGI GABUNGAN KELOMPOK PETANI TANI MAKMUR DAN UKM INDUSTRI ALKOHOL NGOMBAKAN - Happy Mulyani; Ifandari Ifandari; Rahmat Budi Nugroho (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2016)
Organic wastes disposal without sufficient treatment by both Tani Makmur Association Farmer Groups and Alcohol Industry Small and Medium Enterprises in Ngombakan Village and chemical fertilizer application has indicated paddy soil quality decrease in surrounding area. IbM’s implementation as joint business pioneering trial in their organic wastes based fertilizer production is an effective strategy to solve those problems. Mainly, the activity purpose is to transfer technology of organic fertilizer production method from vinasse, cow dung, rice straw, and paddy soil. Thetechnologywhich be transferred consist ofvinasse pre-treatment, rice straw and paddy soil-based bioactivator production and propagation, organic fertilizer production using double composting method from vinasse, cow dung, and rice straw with rice straw and paddy soil-based bioactivator, and its organic fertilizer products application into rice plant. The techology transfer methods used are giving talks & discussion, demonstration & practice, and accompaniment. Event was attended by 25 participants from Tani Makmur Association Farmer Groups and 6 participants from Ngombakan Alcohol Industry Small and Medium Enterprises. In this activity, given 4 liquid organic composter having capacity 60 L, 10 L of bioactivator (consortium of Azotobacter, phosphate solubilizing bacteria, and sellulolitic bacteria), bioactivator propagation tools, 2 pre-treatment vinasse drums having capacity 200 L, and leaflet for each transfer tecnology topics. Results of activity showed an increased the ability to do vinasse pre-treatment for Ngombakan Alcohol Industry Small and Medium Enterprises, and to propagate bioactivator, to produce organic fertilizers, and to apply its products to their rice plant field for the farmers. Keywords:Bioactivator, Cow Dung, Organic Fertilizer, Rice Straw, Vinasse